After metformin, what is the best oral agent for use in patients with type 2 diabetes without comorbidities?. Issue 4 (April 2018) - Ajayi, Olufunke; Satre, Thomas
Abstract : EVIDENCE‐BASED ANSWER : No clear "best oral agent" exists to add to metformin. Sodium‐glucose co‐transporter 2 (SGLT‐2) inhibitors have the best mix of weight, blood pressure, and hypoglycemia reduction compared with other oral agents, but at the expense of more mycotic genital infections (SOR: C, disease‐oriented evidence from meta‐analyses of RCTs). Sulfonylureas, dipeptidyl peptidase‐4 (DPP‐4) inhibitors, thiazolidinediones, and SGLT‐2 inhibitors are all feasible options. The choice of which 1 of these agents should take into account the benefits, adverse effects, and cost (SOR: C, expert opinion).